Case of recurring Kikuchi disease and autoimmune hepatitis. Issue 10 (17th October 2022) - Dhamrah, Umaima; Ireifej, Branden; Ummar, Sibghatallah; Batool, Nuzhat; Song, David; Sheth, Nirali; Shrestha, Abhigan Babu; Jaiswal, Vikash
Abstract: We present a case of a 47‐year‐old female patient with a history of diagnosed Kikuchi disease and autoimmune hepatitis 13 years ago who presented with recurrent fevers and a desquamative rash on the lower extremities. Computed tomography neck showed enlarged lymph nodes, and with her daily fevers and skin rashes the presentation was concerning for recurrence of her Kikuchi disease. The patient was also found to have an elevated anti‐smooth muscle antibody titer, and subsequent liver biopsy confirmed the diagnosis of autoimmune hepatitis. She was started on methylprednisolone with improvement. Our case emphasizes the association of Kikuchi disease with autoimmune conditions other than systemic lupus erythematosus. Given the recurrence of the disease after a decade of quiescence, long‐term follow‐up of patients with Kikuchi disease should be implemented. Abstract : Kikuchi disease (KD) can relapse despite a remission period, with other recurrent autoimmune diseases closely linked. Our case emphasizes the association of KD with autoimmune conditions other than systemic lupus erythematosus (SLE). Given the recurrence of the disease after a decade of quiescence, long‐term follow‐up of patients with KD should be implemented.